Chicken egg yolk antibodies against bovine respiratory syncytial virus neutralize the virus in vitro - Ferella, Alejandra; Bellido, Demian; Chacana, Pablo; Wigdorovitz, Andres; Dus Santos, Maria Jose; Mozgovoj, Marina Valeria (Elsevier, 2019)
5th Vaccine and ISV Annual Global Congress, Seattle, United States of America, 2nd to 4th October 2011